A cross-level study of the relationship between ethical leadership and employee constructive deviance: Effects of moral self-efficacy and psychological safety climate - Shang, Luming; Yang, Lei (Frontiers in Psychology, 2022)
Constructive deviance describes acts that benefit the organization by deviating from outdated organizational norms. Despite emerging interest in this behavior, questions remain about why and how constructive deviance occurs. This paper integrates social learning and uncertainty reduction theories, and develops a multilevel model linking team-level ethical leadership to employee constructive deviance. Surveying 313 subordinates and 52 supervisors from 15 different companies in eastern China, we find that team-level ethical leadership has a positive impact on employee constructive deviance, and that both psychological safety climate and employee moral self-efficacy partially mediate this relationship. In addition, we find a positive cross-level moderating effect of psychological safety climate. These findings contribute to understanding employees’ constructive deviance in the workplace, and provide valuable implications for managerial practices.